EVALUASI SISTEM SURVEILANS TUBERKULOSIS (TB) DI DINAS KESEHATAN KOTA DENPASAR - Zahrah, Tharfi Aufa; Ekaputra, I Wayan Gede Artawan (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024, 2025)
Indonesia is known as a country with a high burden of TB which has contributed to the second most cases in the world since 2019, this has encouraged the government to achieve its main mission to eliminate TB by 2030. The surveillance system as a tool to strengthen the recording and reporting of tuberculosis needs to be evaluated regularly so that the quality of the system itself is maintained. This study aims to evaluate tuberculosis surveillance carried out by the Denpasar City Health Office. This evaluation study was carried out by interviewing using a questionnaire with 26 informants who were TB P2P officers at the Denpasar City Health Office and Primary Healthcare Centers as well as a report study and a desk review of the SITB application. The results of this study found that the recording and reporting of TB cases at the Denpasar City Service was in accordance with the standards as in TB management guidance, although the target had not been reached from year to year. The evaluation results show that the surveillance system has good timeliness, good acceptability, high sensitivity and positive predictive value, and is representative. However, simplicity, flexibility, data quality, and surveillance system stability are lacking. The advice that can be given is to increase the potential of the resources that are already owned by training and reciprocity as well as sufficient budget, consistent supervision and validation, and maximizing the utilization of the data that is owned. Keywords: Evaluation, Tuberculosis, Surveillance Attributes